(3GdcGajIs - (3GdeGdcj GdeUQj GdCSfhj, CHh YeQh, GHf GdMGLH, LeGd GdOjf, YKeGf Hf YeQ Hf CHj HcQ, J(B646(3g`s ((3GfWhf GdecQRds)
(3ChdgG (B:s
(3GdcdeI daX hVY deYfi eaQO hgj GSe haYd hMQa dCfgG EeG Cf JOd Ydi eYfi aj faSgG Ch dG GdKGfj GdMQa GdChd EeG Cf jbJQf HCMO GdCRefI GdKdGKI Ch dG, GdKGfj GdGSes
(3BNQgG (B:s
(3haj Gdhba ajQO eG MPa hGdeaJhMI eG bHdgG JbdH CdaGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 211s
(3eYLe GdeDdajf(B: 2 / 366s
(3cTa GdXfhf(B: 2 / 1370s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs